2014
DOI: 10.1177/1474515114559435
|View full text |Cite
|
Sign up to set email alerts
|

Pocket-sized ultrasound examination of fluid imbalance in patients with heart failure: A pilot and feasibility study of heart failure nurses without prior experience of ultrasonography

Abstract: After brief training, heart failure nurses can reliably identify pulmonary congestion and pleural effusion with a PSUD. Assessment of vena cava inferior was less valid. PSUD readings, when added to the history and a physical examination, can improve nurse assessment of fluid status in patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
27

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(68 citation statements)
references
References 29 publications
4
37
0
27
Order By: Relevance
“…Studies comparing nurses with an expert have shown similar results. In another study by Gustafsson et al 15 four nurses in a heart failure clinic without prior ultrasound experience received 4 h training before they performed scans on 104 patients. The prospective study by Dalen,Gundersen 14 which investigated the IRR between two nurses specialized in cardiovascular nursing and a cardiologist found good agreement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies comparing nurses with an expert have shown similar results. In another study by Gustafsson et al 15 four nurses in a heart failure clinic without prior ultrasound experience received 4 h training before they performed scans on 104 patients. The prospective study by Dalen,Gundersen 14 which investigated the IRR between two nurses specialized in cardiovascular nursing and a cardiologist found good agreement.…”
Section: Discussionmentioning
confidence: 99%
“…15 It may be critical to choose the correct moment for measurements, as previous studies have cautioned against measurements of the IVC for dry weight assessment at treatment cessation, as they may be incorrect due to plasma refilling. This study shows that for this individual, after this period, their scans were reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant literature concerning renal nurses’ use of US to measure the IVC in haemodialysis patients was examined. No articles on renal nurses using US to measure the IVC were found, however several papers have concluded that nurses can successfully use ultrasound in a variety of other clinical settings (Baumann et al ; Schoch & Smith ; Sharp et al ; Dalen et al ; Gustafsson et al ).…”
Section: Use Of Ultrasound By Nursesmentioning
confidence: 99%
“…use ultrasound in a variety of other clinical settings(Baumann et al 2008;Schoch & Smith 2012;Sharp et al 2013;Dalen et al 2014;Gustafsson et al 2014).…”
mentioning
confidence: 99%